Corrigendum: Cysteine residues in signal transduction and its relevance in pancreatic beta cells - Holendova, Blanka; Plecita-Hlavata, Lydie (Frontiers in endocrinology, 2024)
[This corrects the article DOI: 10.3389/fendo.2023.1221520.].
Keywords: pancreatic beta cells; cysteine; posttranslational modifications; thiol; redox signaling